(untitled) (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
Electronic documents are information that is permitted or stored in a way that is requested by a computer or other electronic device to be installed, assigned or processed. These documents consist of text, graphics or spreadsheets. For the current technological developments that improve progress, security is very important in companies that are difficult to avoid the follow-up of information by parties who are not responsible. One method that can be used to obtain digital documents is using Steganography and Cryptography technology by using Discrete Cosine Transform (DCT) technology and Advanced Desktop Encryption Standard (AES-192) algorithm based on Java Desktop. The purpose of this application is to prepare data or files to be hidden on the cover image of the file. Before inserting with the closing image file, the file is encrypted with a symmetrical key using the AES-192 algorithm. The benefits obtained in this application, the confidentiality of information or data on this heavy equipment company can be difficult with good and safe. With this application it is expected to help the confidentiality of information or data on heavy equipment companies. .